Waterlogging and restricted-below ground aeration on photosynthetic performance and root elongation rate of RRIM 600 and RRIT 251 rubber genotypes (Hevea brasiliensis Mull. Arg.) - AIDIL AZHAR; JATE SATHORNKICH; POONPIPOPE KSAMSAI (Universitas Syiah Kuala, 2022)
Due to extended inundation, waterlogging and restricted below-ground aeration cause inhibition in plant growth performance. This study examined two different rubber clones, RRIM 600 and RRIT 251, for waterlogging and restricted below ground aeration. To evaluate the plant performance under the stress conditions, net photosynthetic rate (PN), maximum quantum yield photosystem II (Fv/Fm) and root elongation rate were observed. RRIM 600 has a higher photosynthetic performance under normal conditions. However, the PN rate and Fv/Fm ratio trend showed that RRIM 600 seems to have difficulties recovering after exposure to restricted-below ground aeration. Although RRIT 251 had a lower tendency of PN rate under normal conditions, the PN rate and Fv/Fm ratio of this clone showed fast recovery. RRIT 251 also performed a higher trend of root elongation rate under both stress conditions than RRIM 600.